Inovasi Pembelajaran Inklusi melalui Peningkatan Self Efficacy Guru - Sri Wahyuni Wahyuni; Meta Silfia Novembli; Nisaul Hasanah (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
Teachers who have high self-efficacy tend to have a low level of anxiety and have a positive attitude towards education in which there are children with special needs. Conversely, teachers who have a low level of self-efficacy tend to show a less or not positive attitude when there are children with special needs in the class. The question is how is the teacher's Self-Efficacy level in teaching children with special needs. Based on this description, the research team felt it was important to conduct this research with the aim of looking at the teacher's Self-Efficacy level in teaching children with special needs at school. The research methodology used is library research, with research stages: Preparation of instruments to measure the level of self-efficacy of teachers in teaching children with special needs at school, data collection and analysis of research data. The targeted outputs are scientific articles and research reports. The results of the study show that the teacher's self-efficacy at As-Shofa Elementary School is in the average category. In the Self-Efficacy Sub-Construction (Inclusive Instructional, Collaboration, and Managing Behavior) the Self-Efficacy level of teachers is also in the moderate category, both those who interact directly with children with special needs and those who do not interact directly with children with special needs